Haptoglobin genotype modulates the relationships of glycaemic control with cognitive function in elderly individuals with type 2 diabetes - Guerrero-Berroa, Elizabeth (Diabetologia, 2015)
AIMS/HYPOTHESIS: The purpose of this study was to investigate whether the association of glycaemic control with cognitive function is modulated by the haptoglobin 1-1 (Hp 1-1) genotype in cognitively normal elderly with type 2 diabetes. METHODS: In this cross-sectional study, we examined 793 participants who were genotyped for Hp (80 Hp 1-1 carriers and 713 Hp 1-1 non-carriers) enrolled in the Israel Diabetes and Cognitive Decline (IDCD) study. Glycaemic control was operationally defined by HbA(1c) level. The outcome measures were performance in four cognitive domains (episodic memory, attention/working memory, language/semantic categorisation, executive function) and overall cognition, a composite of the domains. Effect sizes were obtained from hierarchical linear regression analyses for each outcome measure, controlling for demographics, type 2 diabetes-related characteristics, cardiovascular risk factors, and their interactions with Hp genotype. RESULTS: Interaction analyses showed significantly stronger associations of HbA(1c) with poorer cognitive function among Hp 1-1 carriers than non-carriers; attention/working memory (p < 0.001) and overall cognition (p = 0.003). For these two cognitive domains, associations were significant for Hp 1-1 carriers despite the small sample size (p < 0.00001 and p = 0.001, respectively), but not for non-carriers. CONCLUSIONS/INTERPRETATION: Our findings suggest that patients with type 2 diabetes and poor glycaemic control carrying the Hp 1-1 genotype may be at increased risk of cognitive impairment, particularly in the attention/working memory domain. The association of glycaemic control with this domain may indicate cerebrovascular mechanisms.